Effect of Promoters on the Catalytic Activity of the Isomerization Catalyst - nan, nan (Iraqi Journal of Civil Engineering, 2010)
AbstractThe crystalline zeolite, namely faujasite type Y with SiO2/Al2O3 mole ratio of 5 was used as raw material for preparation of isomerization catalysts. Decationized HY-zeolite was prepared by treating Na Y-zeolite with solution of 4N ammonium chloride through ion exchange, drying at 110°C, and calcination initially at 150°C and the temperature increased to 525°C with a rate of 75°C/h to liberate NH3 and water. Then, HY-zeolite was reduced with hydrogen at 380°C, then fabricated as a spherical shape and calcined at 400°C.A 0.5 wt % Pt/HY-zeolite catalyst was prepared by impregnation with chloroplatinic acid. The catalyst was dried at 110°C over night, calcined at 400°C and reduced with hydrogen at 380°C. The prepared catalyst powder was then formulated as a spherical shape with 20% sodium silicate. The decationized HY-zeolite was treated with HCl, HNO3 and HI promoters using different normalities and with different concentrations of Sn, Ni and Ti promoters by impregnation method to obtain acidic and metallic promoters' catalysts, respectively. A 0.5 wt% of Pt was added to above catalysts using impregnation method. The catalysts were then dried, calcined, reduced and formulated using the same steps in preparation of Pt/HY-zeolite catalyst.